Unequal Returns: Gender Differences in Initial Employment Among University Graduates - Hughes, Karen D.; Lowe, Graham S. (Canadian Journal of Higher Education, 1993)
This paper examines how socio-demographic, educational, work attitude, and labour market characteristics contribute to gender differences in the earnings and promotion opportunities of 1985 university graduates employed full-time one year after graduating. Even after accounting for the effects of faculty of enrolment, gender differences in initial employment outcomes are attributable to gender-segregated labour market structures, union and professional association membership, and specific job conditions. Thus, men and women graduating from the same faculty and university translate credentials into different kinds of employment futures. Interestingly, wanting a job with good promotion opportunities at the time of graduation increased the chance of finding such a job, regardless of sex. This paper concludes by exploring the theoretical and policy implications of these findings.